Wrestling with God in Context : Revisiting the Theology and Social Vision of Shoki Coe - Joseph, M. P.; Hsu, Victor; Huang, Po Ho (Book collections on Project MUSE., 2019)
Shoki Coe was among the first to speak of "contextualization" in theology. Coe argued that theology is not a reiteration of past formulas or doctrines but a response to the self-disclosing initiative of the living God in history and human experience. Yet he remains little known outside his native Taiwan. Wresting with God in Context introduces Coe's work and social vision and evaluates his contributions to the field of missiology and ecclesiology. Eager to offer a creative and critical witness to Christian faith, Coe worked tirelessly to liberate theology from its Western captivity and shaped a generation of theological reflection on God, culture, and history. For thousands of students and church members around the world, Shoki Coe was the spiritual father that guided their contextual theological pursuit to the living reality of God. In order to reflect on his legacy, the chapters in this volume--including original essays from Stephen Bevans, Dwight Hopkins, and Enrique Dussel--tackle the critical, methodological issues related to doing theology, reading the Scriptures, and being the church.